Desempenho de novilhas de corte em pastagens de estação quente: uma meta-análise - Martini, Amanda Carneiro (2023)
Meta-analysis is a procedure that combines results from multiple studies to make a reproducible and quantifiable synthesis of data, This technique provides a more robust estimate of the effects of an investigation. To ensure the sustainability of livestock farming, it is necessary selection and containment of beef heifers to maintain herd size and productivity. Therefore the rearing of beef heifers is extremely important, as it is related to the heifers development and, consequently, impacts the age at which the reaches puberty and her reproductive efficiency. However, the biggest challenge is providing nutritional support for the heifers' development. Summer pastures, as well as the provision of supplements, are alternatives that allow animals to gain weight and increase stocking rates. The main objective is to provide explanation and the advantages of meta-analysis as a tool for obtaining more accurate results and on the use of supplements in cultivated warm season pastures for beef heifers.